Industrialized housing in China: a coin with two sides - Zhang, Xiaoling; Skitmore, Martin (International Journal of Strategic Property Management, 2012)
China today is experiencing a time when housing is needed more than ever and one approach satisfying this need is by industrialization – a streamlined process aimed at generating profits and promoting energy efficiency in the housing sectors. Although large housing programs have been completed in China, few housing projects have been built in an industrialized manner. One contributing factor is that industrialization is not omnipotent and, just as a coin has two sides, not all the outcomes of industrialization are beneficial. In this paper, a preliminary assessment is made of these two sides – the benefits and hindrances of industrialized housing in China – by literature review and survey. Case studies are used to verify the questionnaire survey results and from which the advantages and disadvantages involved are compared. The findings indicate the need for formulating policies to encourage industrialized housing in China and for well-planned R&D themes to be implemented simultaneously with industry practices in the near future. First Publish Online: 19 Jun 2012